The geological structure and complex morphological evolution of a regressive barrier at Pinheira, southern Brazil - Sergio R. Dillenburg; Patrick A. Hesp; Eduardo G. Barboza-Pinzon; Maria Luiza C.C. Rosa; Felipe Caron; Rodolfo J. Angulo; Maria C. Souza; Graziela Miot da Silva; Felipe Guadagnin; André O. Sawakuchi (CATENA, 2026)

Coastal Geoheritage in Southern Brazil: Scientific Perspectives from the Northern Coastal Plain of Rio Grande do Sul - Gabriela Camboim Rockett; Samanta da Costa Cristiano; Felipe Caron; Maria Luiza Correa da Camara Rosa; Marco Rossoni; Raquel Barros Binotto; Rafael Frizzo; Luana Portz (Geoheritage, 2026)
The northern sector of the Rio Grande do Sul Coastal Plain, southern Brazil, preserves a detailed record of Quaternary sea-level changes and coastal processes. In this study, 54 geosites were identified and characterized across 18 municipalities, including lagoon-barrier systems, dune fields, coastal ridges, abrasion caves, testimony hills, lagoons, spits, deltas, and shell mounds. These sites document the geological evolution of the region during the last 325,000 years and represent key elements for the reconstruction of paleoenvironments and coastal dynamics. The methodological approach combined cartographic and bibliographic surveys, GIS-based data integration, and fieldwork validation. Results indicate that several geosites have international relevance due to their representativeness, integrity, and rarity, while others provide significant opportunities for education and geotourism. However, many of these sites are located outside legally protected areas, which increases their vulnerability. The analysis emphasizes the importance of integrating geodiversity into conservation and management instruments, reinforcing the role of coastal features as archives of climate change and as providers of ecosystem services. The results provide a scientific basis for geoconservation strategies and support future initiatives, such as the proposal of a geopark focused on the lagoon-barrier systems of southern Brazil.

Late Pleistocene aeolian reactivation in coastal barriers of southern Brazil: stratigraphic expression and paleoclimatic significance - Thiago P. Souza; Maria Luiza C.C. Rosa; Paulo C.F. Giannini; Sérgio R. Dillenburg; Eduardo G. Barboza-Pinzon; Felipe Caron; Juan Sebastian Gomez-Neita; Sergio M.M. Cárdenas; Thais A. Silva; Andre O. Sawakuchi; Renato P. Lopes (Quaternary International, 2026)

Sedimentology, chronology, and evolution of a Pleistocene Barrier (MIS 5) in the North of the Coastal Plain of Rio Grande do Sul, Southern Brazil - Thiago P. Souza; Maria Luiza C.C. Rosa; Paulo C.F. Giannini; Sérgio R. Dillenburg; Eduardo G. Barboza-Pinzon; Felipe Caron; Juan Sebastian Gomez-Neita; Sergio M.M. Cárdenas; Gilberto S. Santos (Quaternary Science Reviews, 2026)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

The progradational Curumim barrier in southern Brazil: An archive of sea-level changes, and cyclic aeolian activity in the Holocene - Sergio R. Dillenburg; Eduardo G. Barboza; Patrick A. Hesp; Maria Luiza C.C. Rosa; Felipe Caron; Felipe Guadagnin (Geomorphology, 2024)

Paleoclimatic and paleoenvironmental significance of late Pleistocene pedogenic carbonates (‘Caliche Cordão’) from the coastal Pampa of southern Brazil - Renato P. Lopes; Jamil C. Pereira; Sergio R. Dillenburg; Alcides N. Sial; Sonia H. Tatumi; Marcio Yee; Felipe Guadagnin; Felipe Caron (Quaternary Science Reviews, 2024)

Inlet migration during the turning point between transgressive and regressive stages at the Guaratuba Holocene barrier, Paraná - Southern Brazil - Marcelo Bogo; Maria Cristina de Souza; Rodolfo José Angulo; Eduardo Guimarães Barboza; Maria Luiza Correa da Camara Rosa; Felipe Caron; Augusto Luiz Ferreira; Shaiely Fernandes dos Santos (Marine Geology, 2023)

Atlantic flower–invertebrate interactions: A data set of occurrence and frequency of floral visits - Danilo Boscolo; Bárbara Nobrega Rodrigues; Patrícia Alves Ferreira; Luciano Elsinor Lopes; Vinicius Rodrigues Tonetti; Isabela Cristhina Reis dos Santos; Juliana Akemi Hiruma‐Lima; Laura Nery; Karoline Baptista de Lima; Jéssica Perozi; André Victor Lucci Freitas; Blandina Felipe Viana; et al. (Ecology, 2023)
Encounters between flowers and invertebrates are key events for the functioning of tropical forests. Assessing the structure of networks composed of the interactions between those partners leads to a better understanding of ecosystem functioning and the effects of environmental factors on ecological processes. Gathering such data is, however, costly and time‐consuming, especially in the highly diverse tropics. We aimed to provide a comprehensive repository of available flower–invertebrate interaction information for the Atlantic Forest, a South American tropical forest domain. Data were obtained from published works and “gray literature,” such as theses and dissertations, as well as self‐reports by co‐authors. The data set has ~18,000 interaction records forming 482 networks, each containing between one and 1061 interaction links. Each network was sampled for about 200 h or less, with few exceptions. A total of 641 plant genera within 136 different families and 39 orders were reported, with the most abundant and rich families being Asteraceae, Fabaceae, and Rubiaceae. Invertebrates interacting with these plants were all arthropods from 10 orders, 129 families, and 581 genera, comprising 2419 morphotypes (including 988 named species). Hymenoptera was the most abundant and diverse order, with at least six times more records than the second‐ranked order (Lepidoptera). The complete data set shows Hymenoptera interacting with all plant orders and also shows Diptera, Lepidoptera, Coleoptera, and Hemiptera to be important nodes. Among plants, Asterales and Fabales had the highest number of interactions. The best sampled environment was forest (~8000 records), followed by pastures and crops. Savanna, grasslands, and urban environments (among others) were also reported, indicating a wide range of approaches dedicated to collecting flower–invertebrate interaction data in the Atlantic Forest domain. Nevertheless, most reported data were from forest understory or lower strata, indicating a knowledge gap about flower–invertebrate interactions at the canopy. Also, access to remote regions remains a limitation, generating sampling bias across the geographical range of the Atlantic Forest. Future studies in these continuous and hard‐to‐access forested areas will yield important new information regarding the interactions between flowers and invertebrates in the Atlantic Forest. There are no copyright restrictions on the data set. Please cite this data paper if the data are used in publications and teaching events.

Correction to: Sedimentary records of Marine Isotopic Stage 3 (MIS 3) in southern Brazil - Sergio R. Dillenburg; Eduardo G. Barboza; Maria Luiza C. C. Rosa; Felipe Caron; Rodrigo Cancelli; Cristiane B. Santos-Fischer; Renato P. Lopes; Matias do Nascimento Ritter (Geo-Marine Letters, 2020)

Sedimentary records of Marine Isotopic Stage 3 (MIS 3) in southern Brazil - Sergio R. Dillenburg; Eduardo G. Barboza; Maria Luiza C. C. Rosa; Felipe Caron; Rodrigo Cancelli; Cristiane B. Santos-Fischer; Renato P. Lopes; Matias do Nascimento Ritter (Geo-Marine Letters, 2020)